Urgensi Spiritual Formation dalam Pemakaian Spiritual Igredient di Working Hypothesis pada Pembelajaran Mahasiswa - Yeffry Hendra Lesmana; Dyulius Thomas Bilo (Sabda: Jurnal Teologi Kristen, 2025)
This study examines the urgency of spiritual formation in the application of spiritual ingredients to the working hypothesis to improve student learning. The focus of this study is to answer the need for a holistic approach in education that is not only centered on cognitive aspects, but also spiritual and emotional. This study formulates the main question: How can the application of spiritual formation through spiritual ingredients strengthen the working hypothesis in the context of student learning? The method used is a literature review with a descriptive qualitative approach. The findings show that the integration of spiritual ingredients in the working hypothesis helps students develop a more reflective and transformative learning approach. This has a positive impact on their ability to face academic and personal life challenges. This study suggests the need for special training for lecturers in integrating spiritual values into teaching, as well as the development of a curriculum that explicitly considers spiritual aspects. The conclusions drawn emphasize that strong spiritual formation can be an important foundation in student learning to build holistic integrity and character.  AbstrakPenelitian ini mengkaji urgensi spiritual formation dalam penerapan spiritual ingredients pada working hypothesis untuk meningkatkan pembelajaran mahasiswa. Fokus penelitian ini adalah menjawab kebutuhan terhadap pendekatan holistik dalam pendidikan yang tidak hanya berpusat pada aspek kognitif, tetapi juga spiritual dan emosional. Penelitian ini merumuskan pertanyaan utama: Bagaimana penerapan spiritual formation melalui spiritual ingredients dapat memperkuat working hypothesis dalam konteks pembelajaran mahasiswa? Metode yang digunakan adalah kajian literatur dengan pendekatan kualitatif deskriptif. Hasil temuan menunjukkan bahwa integrasi spiritual ingredients dalam working hypothesis membantu mahasiswa mengembangkan pendekatan pembelajaran yang lebih reflektif dan transformatif. Hal ini berdampak positif pada kemampuan mereka dalam menghadapi tantangan akademik dan kehidupan pribadi. Penelitian ini menyarankan perlunya pelatihan khusus bagi dosen dalam mengintegrasikan nilai-nilai spiritual ke dalam pengajaran, serta pengembangan kurikulum yang memperhatikan aspek spiritual secara eksplisit. Kesimpulan yang dihasilkan menekankan bahwa pembentukan spiritual yang kuat dapat menjadi fondasi penting dalam pembelajaran mahasiswa untuk membangun integritas dan karakter holistik.Kata Kunci :Spiritual Formation, Spiritual ingredient, working hypothesis, pola pembelajaran